2019
DOI: 10.1371/journal.pone.0217254
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characteristics of propofol-induced inhibition of electron-transfer chain and fatty acid oxidation in human and rodent skeletal and cardiac muscles

Abstract: IntroductionPropofol causes a profound inhibition of fatty acid oxidation and reduces spare electron transfer chain capacity in a range of human and rodent cells and tissues–a feature that might be related to the pathogenesis of Propofol Infusion Syndrome. We aimed to explore the mechanism of propofol-induced alteration of bioenergetic pathways by describing its kinetic characteristics.MethodsWe obtained samples of skeletal and cardiac muscle from Wistar rat (n = 3) and human subjects: vastus lateralis from hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The unsaturated fatty acids decreased and saturated fatty acids increased, and were relatively unaffected by addition of propofol (1.75 to 17.5 μgl −1 ) in in vitro analysis (Appendix B, http://links.lww.com/EJA/A604). Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO) 37,38 . On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unsaturated fatty acids decreased and saturated fatty acids increased, and were relatively unaffected by addition of propofol (1.75 to 17.5 μgl −1 ) in in vitro analysis (Appendix B, http://links.lww.com/EJA/A604). Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO) 37,38 . On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies on human skeletal and heart muscle cell bioenergetics have shown a profound inhibitory effect of propofol on fatty acid oxidation (FAO). 37,38 On the basis of previous research, after an overnight fast, FAO may account for up to 70% of total body energy expenditure. 39 In theory, a disruption of fatty acid utilisation could lead to changes in the circulating lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been shown to impair mitochondrial function via the inhibition of complex II + III activity in an in vivo rat model [69]. Moreover, propofol can inhibit fatty acid oxidation and the flux of electrons through the inner mitochondrial membrane, which is more pronounced in human than rat tissue [70] and can attenuate mitochondrial membrane potential in differentiated C2C12 cells [71]. In contrast, pregabalin has not previously been cited as causing mitochondrial dysfunction in vivo or in vitro skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“… 45 In vitro , clinically relevant concentrations of propofol directly inhibited FAO and mitochondrial respiration in human heart and skeletal muscle. 46 Physiologically, elevated 12,13-DiHOME in response to exercise increased fatty acid uptake to skeletal and cardiac myocytes, increasing FAO. 28 In high concentrations, DiHOMEs induce mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%